2018
DOI: 10.1152/physiol.00024.2018
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Ovarian Hormones and Accelerated Somatic and Mental Aging

Abstract: Bilateral oophorectomy in premenopausal women is a unique condition causing the abrupt and premature loss of ovarian hormones, primarily estrogen. Bilateral oophorectomy causes an alteration of several fundamental aging processes at the cellular, tissue, organ, and system levels, leading to multimorbidity, frailty, and reduced survival. However, many questions remain unanswered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 50 publications
3
40
0
Order By: Relevance
“…In addition, it is possible that in contrast to our findings in young adult mice, sex steroid deficiency may result in senescent cell accumulation in middle‐aged mice, which should be tested in future studies. Interestingly, it appears that long‐term estrogen deficiency in women who had ovariectomies as young adults can experience accelerated development of aging phenotypes once these women are much older . Thus, it remains at least formally possible that estrogen deficiency over decades could turn out to be associated with an increase in senescent cell accumulation, a speculation that warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, it is possible that in contrast to our findings in young adult mice, sex steroid deficiency may result in senescent cell accumulation in middle‐aged mice, which should be tested in future studies. Interestingly, it appears that long‐term estrogen deficiency in women who had ovariectomies as young adults can experience accelerated development of aging phenotypes once these women are much older . Thus, it remains at least formally possible that estrogen deficiency over decades could turn out to be associated with an increase in senescent cell accumulation, a speculation that warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it appears that long-term estrogen deficiency in women who had ovariectomies as young adults can experience accelerated development of aging phenotypes once these women are much older. (24) Thus, it remains at least formally possible that estrogen deficiency over decades could turn out to be associated with an increase in senescent cell accumulation, a speculation that warrants further investigation. Finally, it will be interesting in future studies to establish whether accelerated cellular aging occurs with sex steroid deficiency as it relates to other hallmarks of skeletal aging, (8) including genomic instability (eg, impaired DNA repair) and mitochondrial dysfunction (eg, oxidative stress).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Longitudinal data from defined cohorts of women will help to identify mechanisms by which changes in the hormonal milieu contribute to cerebrovascular ageing, brain structure and ultimately cognition. This review summarises the phenotypes of three cohorts of women identified through the medical records‐linkage system of the Rochester Epidemiology Project (REP) and the Mayo Clinic Specialized Center of Research Excellence (SCORE) on Sex Differences: (i) menopausal women with histories of normotensive or hypertensive pregnancies; (ii) women who had bilateral oophorectomy ≤45 years of age; and (iii) women who experienced natural menopause and used menopausal hormone treatments for 4 years . Cardiovascular risk factors, cardiovascular structure, cerebrovascular reactivity, brain structure and cognition were examined in each of these cohorts.…”
Section: Introductionmentioning
confidence: 99%